Hygiene and health - Llewellyn, Claire (Laguna Hills, CA : QEB Pub., 2006)
An exploration of health and hygiene for children that identifies ways to stay healthy, discusses germs, and provides activities that reinforce the topics covered.
Includes index.
2.8
K-3
Keywords: Children -- Health and hygiene -- Juvenile literature; Cleanliness; Health; Health; Hygiene